Global, regional, and national burden and quality of care index of endocarditis: the global burden of disease study 1990–2019 - Sara Momtazmanesh; Sahar Saeedi Moghaddam; Elaheh Malakan Rad; Sina Azadnajafabad; Narges Ebrahimi; Esmaeil Mohammadi; Mahtab Rouhifard; Negar Rezaei; Masoud Masinaei; Nazila Rezaei; Mohammad Keykhaei; Arya Aminorroaya; et al. (European Journal of Preventive Cardiology, 2022)
Endocarditis accounts for significant morbidity and mortality. Timely diagnosis and prompt treatment are of paramount importance for optimal patient outcome. However, only few studies have assessed quality of care (QoC) in endocarditis. We aimed to describe QoC and changes in epidemiological features of endocarditis from 1990 to 2019. Using primary indices of mortality, incidence, years of life lost, years lived with disability, and disability-adjusted life year, obtained from the Global Burden of Disease Study 2019, we calculated four secondary measures. Principal component analysis was performed to calculate QoC index (QCI), scored on a scale of 0–100 with higher values indicating better QoC, for different locations, age groups, and genders from 1990 to 2019. The all-ages incidence rate of endocarditis was estimated to increase significantly from 1990 to 2019, while mortality rate did not change. The age-standardized QCI was 73.6% globally, with higher values in high-income countries than in low-income countries. High-income North America (82.0%) and Asia Pacific (81.1%) had the highest QCI, whereas Eastern Europe (43.3%) had the lowest. Globally, the 30–49 and 95+ age groups had the highest (91.3%) and the lowest (71.7%) QCI, respectively. In most countries, particularly those with lower socio-demographic index, women had better QCI. This is the first global assessment of QCI, shedding light on the current trends and highlighting the necessity of improving the endocarditis QoC, mainly by timely case detection, adherence to antibiotic prophylaxis guidelines, utilizing targeted antibiotics and advanced treatments, in the African region and resolving gender inequality in selected countries.
Keywords: 330; Burden; Cardiovascular diseases; Endocarditis; Epidemiology; Health status indicators; Quality of health care